An empirical analysis of the risk behaviour of postgraduate studenrs - Bhugaloo, Shahin (2008)
The role of risk is a topic that has increasingly attracted the attention of both scholars and practitioners. This is so because risk taking is an integral part of business and life. This research attempts to describe the risk behaviour of postgraduate students. This segment is chosen to be studied because they represent the consumers, future managers and entrepreneurs of the economy. The research is conducted through an experiment, which tests the participants risk behaviour individually and in pairs. Data is collected via a questionnaire, with counterbalancing effects, and then input and analysed using SPSS 13.0. Risk attitudes of participants are observed given their responses. The results demonstrate the risk preferences of participants, and the risk behaviour in groups as compared to risk taking individually. The degree of risk averseness and risk lovingness is also taken into account. Some cultural differences are observed. Recommendations are mostly based around insurance techniques because of the loss framework adopted in the research instrument. However, risk attitudes are also used to recommend risk management and other strategies in firms.